ANÁLISE PROBABILÍSTICA DA CONFORMIDADE DE TENSÃO EM REDES DE DISTRIBUIÇÃO CONSIDERANDO A PRESENÇA DE GERAÇÃO DISTRIBUÍDA. - VIEIRA, Carlos Henrique da Silva (2012)
Currently, there is growing concern about the Power Quality (PQ) problems due to: introduction of automation in industrial processes, presence of personal computers and electronically controlled devices, load equipments with low capacity to withstand small PQ disturbances and increased perception of residential and industrial consumers with regard to PQ disturbances. In this context, an important issue with relation to PQ is the voltage conformity. That is, the adequacy of service voltage to the limits specified by regulatory agencies. The concern about compliance is due to the following problems caused by sustained undervoltages and overvoltages: improper or less-efficient equipment operation, tripping of sensitive loads, overheating of induction motors due to undervoltages, equipment damage or failure due to overvoltages and higher no-load losses in transformers caused by sustained overvoltages. Furthermore, there have been various incentives for connection of Distributed Generation (DG) in distribution networks due to: incentives for the using of electricity generation based on renewable energy sources and free access of independent energy producers to transmission and distribution networks owing to deregulation of the electric sector. In principle, the voltage profile of a distribution network can be improved with connection of DG. However, it is possible to notice severe deteriorations in the voltage profile of distribution networks in DG post-failure scenarios. These failures are caused by problems in the DG components, such as: cooling system, gears, turbines, etc. During the time period in which the DG is under repair, active and reactive power supports to correct the voltage profile are unavailable. Consequently, the voltage profile tends to deteriorate while the DG is disconnected. In this way, it is important to carry out studies to assess the impact of the DG installation on the voltage conformity indices considering the following issues: DG unavailability after an intrinsic failure and load curve. These aspects are subject to uncertainties due its random nature. Due to this, the most suitable approaches to assess the impact of uncertainties associated with load fluctuations and DG failures on the voltage conformity indices are the probabilistic methods. The main advantage of these methods is its capability to combine severity and probability to truly express the system risk. The main objective of this dissertation is the development of a method that models the random behavior of the distribution network in the voltage conformity indices estimation through the probabilistic methods. Models and techniques to incorporate stochastic variations in the demand and DG unavailability in voltage conformity indices estimation are proposed. The technique proposed in this dissertation to carry a Predictive Assessment of Voltage Conformity (PAVC) is based on the combination of the following techniques: power flow for radial distribution networks via current summation method, Quasi-Sequential Monte Carlo Simulation and Fourier analysis of time series. The PAVC model proposed in this dissertation was tested in 32 buses system. The results obtained with this system demonstrated that the DG has a great potential to improve the voltage conformity indices in the distribution network. However, the most significant improvements in the voltage conformity indices are associated with load points distant from the substation. Furthermore, it can be observed that the uncertainties associated with DG failures cause significant variations in the voltage conformity indices. Additionally, a sensitivity study demonstrated that the voltage conformity indices are worse (better) for systems where the load is modeled as constant power (impedance).